Production and effects of nanomineral selenium (Nano-Se) feed additive on rumen fermentation, productivity, and reproductive performance of ruminants. (Journal of Advanced Veterinary and Animal Research, 2024)
Nanotechnology (Nano) applications of feed additives can potentially improve feed-substrate efficiency to enhance livestock productivity. The utilization of Nano in feed in ruminants still tends to be under-explored and reviewed, particularly the application of Nano in trace minerals to enhance the reproductive performance and productivity of ruminants such as selenium. Trace minerals are essential for animal well-being and productivity, and the bioavailability of trace minerals is influenced by a complex matrix of interacting variables, including the chemical form of the minerals used and those found in the diet, the nature of the food ingested, the total composition of the diet, and the health and nutrition of the livestock. Nanominerals such as selenium (nano-Se) have shown impressive results when used as animal feed supplements in ruminants. Nano-Se can significantly boost wellness and immunity, gastrointestinal system function, microbiota homeostasis, metabolism, and reproductive performance in ruminants. This review aims to present the current knowledge on the technology of nano-Se in ruminants, ranging from the nanomanufacturing procedures of nano-Se, the impact of supplementation on the ruminant digestive system, productivity, and reproductive performance in ruminants in some dosages to find the optimized dosage to be provided.J. Adv. Vet. Anim. Res., 11(3): 782-795, September 2024http://doi.org/10.5455/javar.2024.k830